Restored connectivity facilitates recruitment by an endemic large‐seeded tree in a fragmented tropical landscape - Marinés de la Peña‐Domene; Emily S. Minor; Henry F. Howe (Ecology, 2016)
Many large‐seeded Neotropical trees depend on a limited guild of animals for seed dispersal. Fragmented landscapes reduce animal abundance and movement, limiting seed dispersal between distant forest remnants. In 2006, experimental plantings were established in pasture to determine whether plantings enhance seed dispersal and, ultimately, seedling recruitment. We examined patterns of naturally recruited seedlings of Ocotea uxpanapana, a large‐seeded bird‐dispersed tree endemic to southern Mexico that occurs in the surrounding landscape. We used GIS and least‐cost path analysis to ask: (1) Do restoration efforts alter recruitment patterns? (2) What is the importance of canopy cover and likely dispersal pathways to establishment? Patterns of seedling establishment indicated that dispersal agents crossed open pastures to wooded plots. Recruitment was greatest under woody canopies. Also, by reducing movement cost or risk for seed dispersers, wooded canopies increased influx of large, animal‐dispersed seeds, thereby restoring a degree of functional connectivity to the landscape. Together, canopy openness and path distance from potential parent trees in the surrounding landscape explained 73% of the variance in O. uxpanapana seedling distribution. Preliminary results suggest that strategic fenced plantings in pastures increase dispersal and establishment of large‐seeded trees, thereby accelerating forest succession in restorations and contributing to greater connectivity among forest fragments.